Signifikansi Hadis Riwayat Dalam Menangani Konten Negatif Di Media Sosial - Azmi Fauziah Suanda; Tajul Arifin (Pusat Riset dan Inovasi Nasional, 2024)
In the digital era filled with social media, the spread of negative content has become a phenomenon threatening the integrity and security of the digital environment. This paper outlines the impact and challenges of disseminating negative content and reviews efforts to address it from the perspectives of Islamic law and positive law, emphasizing the importance of the hadith of Prophet Muhammad (peace be upon him) stating,